ANALISIS BRAND POSITIONING SEPEDA MOTOR HONDA DAN YAMAHA PADA PENGGUNA SEPEDA MOTOR DI PROVINSI BANTEN - Sutisna, Sutisna (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research analyzes the brand positioning of Honda and Yamaha motorbikes in Banten Province. Brand positioning is a key element in marketing that depicts a unique value proposition to consumers. This study uses a comparative descriptive method with data collected through questionnaires to 151 respondents. The sampling technique used was convenience sampling. The research results show that Honda's brand positioning, with the tagline "One Heart", is stronger than Yamaha's with the tagline "Getting ahead". The analysis shows that consumer perceptions of Honda's brand positioning are higher (average score 3.58) than Yamaha (average score 3.47). The mean difference test shows a significant difference between the two brands. Consistency in the use of taglines in promotions has proven effective in establishing brand positioning in the minds of consumers. This study provides insight for manufacturers in designing appropriate marketing communications to build strong brand positioning, as well as the importance of maintaining consistency in promotional strategies. This research is useful for Honda and Yamaha to understand consumer perceptions and improve their marketing strategies